An updated review on phytochemistry and molecular targets of Withania somnifera (L.) Dunal (Ashwagandha) - Bashir, Arsalan; Nabi, Masarat; Tabassum, Nahida; Afzal, Suhaib; Ayoub, Mehrose (Frontiers in Pharmacology, 2023)
Withania somnifera (L.) Dunal belongs to the nightshade family Solanaceae and is commonly known as Ashwagandha. It is pharmacologically a significant medicinal plant of the Indian sub-continent, used in Ayurvedic and indigenous systems of medicine for more than 3000 years. It is a rich reservoir of pharmaceutically bioactive constituents known as withanolides (a group of 300 naturally occurring C-28 steroidal lactones with an ergostane-based skeleton). Most of the biological activities of W. somnifera have been attributed to two key withanolides, namely withaferin-A and withanolide-D. In addition, bioactive constituents such as withanosides, sitoindosides, steroidal lactones, and alkaloids are also present with a broad spectrum of therapeutic potential. Several research groups worldwide have discovered various molecular targets of W. somnifera, such as inhibiting the activation of nuclear factor kappa-B and promoting apoptosis of cancer cells. It also enhances dopaminergic D2 receptor activity (relief in Parkinson’s disease). The active principles such as sitoindosides VII-X and withaferin-A possess free radical properties. Withanolide-D increases the radio sensitivity of human cancer cells via inhibiting deoxyribonucleic acid (DNA) damage to non-homologous end-joining repair (NHEJ) pathways. Withanolide-V may serve as a potential inhibitor against the main protease (Mpro) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to combat COVID. The molecular docking studies revealed that the withanolide-A inhibits acetyl-cholinesterase in the brain, which could be a potential drug to treat Alzheimer’s disease. Besides, withanolide-A reduces the expression of the N-methyl-D-aspartate (NMDA) receptor, which is responsible for memory loss in epileptic rats. This review demonstrates that W. somnifera is a rich source of withanolides and other bioactive constituents, which can be used as a safe drug for various chronic diseases due to the minimal side effects in various pre-clinical studies. These results are interesting and signify that more clinical trials should be conducted to prove the efficacy and other potential therapeutic effects in human settings.